If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying xy + 3y = m Solving xy + 3y = m Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3y' to each side of the equation. xy + 3y + -3y = m + -3y Combine like terms: 3y + -3y = 0 xy + 0 = m + -3y xy = m + -3y Divide each side by 'y'. x = my-1 + -3 Simplifying x = my-1 + -3 Reorder the terms: x = -3 + my-1
| -2=8(x) | | x^2-(2x)-3=0 | | x+3(4x-2)=7x-1 | | x^2-7=x^2-6x-7 | | 6(2dx+y)=11dx-7y | | -7x+4x+19-12x= | | 20=-5d | | 2(ax+3)=4c | | 4x+7=x+46 | | 3(0)+9y=18 | | 2(4x+1)=2x-9x | | 3x+9(0)=18 | | 40-60x=-10(6x-4) | | 5x-0.5(3x+8)=-4+3x | | -14x-2=14x+7+8 | | 13-5m=4-6m+m | | -4g-4=2g | | -14-6y=-2 | | 5(0)-3y=15 | | 9(x+4)+4(x+4)=6x-6 | | 20x+54.1=45.9 | | -8=4+.125b | | 3x+9-x=35 | | 9x-18=8x-18 | | 5x=4.8 | | 20x-1=10x+1 | | 2x-x+9=-6 | | 5x=.03 | | 2x(x-3)=8x^2-7x | | 13(x-1)=8x+22 | | 3(5x-2)+4=11x-3-4x | | 0-y=-1 |